EXERCISE DURING PREGNANCY - Zrna Agačević; Muhedin Hodžić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Exercise has become a vital part of many women's lives. However, theoretic concerns have been raised about the safety of some forms of exercise during pregnancy. Because of the physiologic changes associated with pregnancy, as well as the hemodynamic response to exercise, some precautions should be observed. The physician should screen for any contraindications to exercise and encourage patients to avoid overly vigorous activity, especially in the third trimester, when most pregnant women have a decreased tolerance for weight-bearing exercise. Adequate hydration and appropriate ventilation are important in preventing the possible teratogenic effects of overheating. Pregnant women should avoid exercise that involves the risk of abdominal trauma, falls or excessive joint stress, as in contact sports and vigorous racquet sports. In the absence of any obstetric or medical complications, most women can maintain a regular exercise regimen during pregnancy. Some studies have found a greater sense of well-being, shorter labor and fewer obstetric interventions in physically wellconditioned women as compared with other women.